SPEED TOOL INNOVATION FOR ROUTINE MAINTENANCE OF PERSONAL PROTECTIVE EQUIPMENT - M. Fadli Fadli; Thursina Handayani (Journal of Airport Engineering Technology (JAET), 2026)
Personal Protective Equipment (PPE) is critical for Airport Rescue and Fire Fighting (ARFF) personnel, yet its maintenance—particularly drying—remains manual and weather-dependent, creating risks of microbial growth and reduced protective effectiveness. This study developed the SPEED device (Effective, Efficient, and Powerful PPE Drying System) using a Research and Development (R&D) approach with the ADDIE model. Data were collected through observation, interviews, and expert validation at the ARFF Unit of Yogyakarta International Airport. SPEED integrates a heating element, exhaust fan, and UV-C lamp (344 W total) with automatic temperature and timer control. Expert validation by three ARFF practitioners and one academic validator yielded a score of 100% ("Very Feasible"). Performance testing confirmed that SPEED dries PPE within 15–60 minutes, up to 16 times faster than conventional sun-drying (180–240 minutes). This innovation improves PPE maintenance efficiency, ensures hygiene, and supports ARFF operational readiness.